Political Purposes, Anti-entrenchment and Judicial Protection of the Democratic Process. (15th October 2021) - Rowbottom, Jacob
Abstract: The legality of decisions made for political purposes is a recurring issue in administrative law. In this article, it will be argued that generalisations should not be made about 'political' decisions as a single category. Instead, there are different types of political consideration, which raise different issues when assessing the legality of a decision. This article singles out a particular type of political decision for condemnation: decisions made to gain a political advantage by deliberately changing the systems of democratic accountability. Examples include the engineering of the electoral system to produce favourable results, the use of public power to punish critics and the use of public resources to publish partisan propaganda. The article will argue that the legality of such political decisions should not be assessed solely within the ordinary administrative law framework, but under a constitutional principle of anti-entrenchment and process protection.